1993
DOI: 10.1152/ajpheart.1993.265.2.h439
|View full text |Cite
|
Sign up to set email alerts
|

Spatial features of calcium transients during early and delayed afterdepolarizations

Abstract: Although changes in intracellular Ca2+ concentration ([Ca2+]i) are spatially heterogeneous during spontaneous contraction in mammalian cardiac muscle, it has not yet been observed how [Ca2+]i changes spatially within cardiac myocytes during delayed (DADs) and early (EADs) afterdepolarizations. The aim of this study is to characterize the spatial features of the increase in [Ca2+]i during such afterdepolarizations and to understand the ionic mechanisms responsible for them. Myocytes were enzymatically isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 0 publications
5
36
0
Order By: Relevance
“…Previously, we reported that the spatial features of increases in [Ca2+]i were spatially synchronous within myocytes when EADs arose from the second phase of an action potential and that the most probable candidate for the subcellular mechanism of this type of EAD was the inward Ca 2+ "window" current through the L-type calcium channel [10]. Because the L-type calcium channel is known to be inactivated completely near -4 0 m V [5,6,11], the following question was raised: are the Spatial features of [Ca2+]i also spatially synchronous during EADs arising from the membrane potential at which the L-type calcium channel is completely inactivated?…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported that the spatial features of increases in [Ca2+]i were spatially synchronous within myocytes when EADs arose from the second phase of an action potential and that the most probable candidate for the subcellular mechanism of this type of EAD was the inward Ca 2+ "window" current through the L-type calcium channel [10]. Because the L-type calcium channel is known to be inactivated completely near -4 0 m V [5,6,11], the following question was raised: are the Spatial features of [Ca2+]i also spatially synchronous during EADs arising from the membrane potential at which the L-type calcium channel is completely inactivated?…”
Section: Introductionmentioning
confidence: 98%
“…They occur when repolarization is complete and are thought to be caused by intracellular Ca 2ϩ oscillations (46) due to Ca 2ϩ release from the sarcoplasmic reticulum (SR) (56). Afterdepolarizations occur in pathological states including heart failure, diabetes, and ischemic heart disease (67, 79, 94) as well as under healthy conditions during increased sympathetic tone, exercise, hypokalemia, and rapid heart rate (9,59,87 -activated Cl Ϫ or nonspecific ion current, thus leading to depolarization of the membrane, a DAD, which could then trigger the initiation of an action potential (AP) by activating the fast Na ϩ current. Figure 1 shows an example of Na ϩ and Ca 2ϩ overload triggering DADs in a mathematical model.…”
mentioning
confidence: 99%
“…They occur when repolarization is complete and are thought to be caused by intracellular Ca 2ϩ oscillations (46) due to Ca 2ϩ release from the sarcoplasmic reticulum (SR) (56). Afterdepolarizations occur in pathological states including heart failure, diabetes, and ischemic heart disease (67,79,94) as well as under healthy conditions during increased sympathetic tone, exercise, hypokalemia, and rapid heart rate (9,59,87). In most experimental setups, Ca 2ϩ overload of the cell was used to induce DADs [see, e.g., Orchard et al (70) and Wier et al (100)] (Table 1), although there have been instances when DADs were found when applying stretch (89), perhaps involving a stretch-induced increase in ryanodine receptor (RyR) open probability and leak in SR Ca 2ϩ (Ca SR ) (31,33).…”
mentioning
confidence: 99%
“…Subsequently, several investigators, using different methods, have studied the spatiotemporal aspects of spontaneous increases in [Ca 2ϩ ] i , [Ca 2ϩ ] i propagation, and resulting membrane depolarizations. For example, using ouabain or potassium-free solutions in single myocytes, Miura et al 19 showed the concomitant occurrence of propagating Ca 2ϩ waves, cell shortening, and membrane depolarization, which is referred to as a delayed afterdepolarization.…”
mentioning
confidence: 99%
“…Again, this finding is consistent with observations in Ca 2ϩ -loaded myocytes. 19 Finally, Kaneko et al 21 report the presence of a third pattern of spontaneous Ca 2ϩ waves (agonal waves) in regions of the intact heart that had been overtly damaged by microelectrode impalement. Agonal waves occur at high frequency over a small extent throughout cells.…”
mentioning
confidence: 99%